Theatres of Torture: Martyrs, Pagans, and the Politics of Conversion in Early Seventeenth-Century France*. Issue 1 (July 2015) - Meere, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> This essay examines writing about and representations of pain and torture by looking specifically at two French Catholic martyr plays that appeared at the turn of the seventeenth century: Nicolas Soret's La Céciliade (1606) and Jean Boissin de Gallardon's Le Martyre de saincte Catherine (1618). It interprets these plays alongside Antonio Gallonio's Trattato degli instrumenti di martiro (1591; 1594) and Richard Verstegan's Théâtre des cruautez des Herectiques de nostre temps (1587; 1607). On the one hand, by analysing the representations of physical torture, this article investigates the relationship between religious violence in the real world and the significance of the martyr figure on stage in La Céciliade. On the other, it takes into account the crushing of the executioners' bodies in Boissin's play and in iconographical representations of St Catherine's wheel of torture, arguing that representations of the martyrs' and pagans' injured bodies not only serve to profess publicly the truth of the Catholic faith but also act as vehicles for the Catholic Church's politicization of martyrdom and conversion.